The relationship between public housing wait lists, public housing tenure and labour market outcomes - Wood, G; Ong, R; Dockery, A.M.; Whelan, S (My University, 2008)
In part this lack of evidence is because public housing is not a program targeted at addressing specific disadvantages or to achieving specific outcomes for its participants. Rather, it is designed to offer a broad safety net to people facing social marginalisation through any of a wide range of adverse circumstances, from low income to physical and mental disabilities, to risks such as domestic violence. In greater part, the paucity of evaluation studies reflects the considerable methodological challenges in the empirical identification of the impact of public housing on social and economic outcomes, and that data required to support such analyses have not been available to Australian researchers. In recent years there has been a growing overseas literature that explores whether public housing impacts on employment outcomes. Studies have put forth opposing arguments as to whether the provision of public housing has positive or negative employment effects on tenants, but here too the empirical evidence remains inconclusive.
Research Report No. 9
Keywords: Housing -- Government. Assistance; Income & Finance -- Income (Salary and Wages); Income, wealth and finances; Income & Finance; Housing; Income (Salary and Wages); Government. Assistance; Income, wealth and finances